Innovation System Laraku Nyata (Population Administration Service for Persons with Disabilities) Bulukumba Regency - Andi Fitriyani Yahya; Alsry Mulyani (Inovbook Publications, 2021)
Population documents generated from the population administration process are the right of every citizen, this is inversely proportional to Indonesian citizens with disabilities, this can happen for several reasons, including difficulty accessing services, the view that people with disabilities are not important to have documents. Population and the lack of information related to disabilities in the population administration process, so that this is the background for innovation, so that persons with disabilities have the right to have a residency identity . The method used in this research is descriptive conducted interviews with several resource persons with qualitative analysis, the results obtained show that there is an increase in the number of persons with disabilities who already have e-KTPs increased sharply from 2016, the ownership of e-KTPs from 85 people, increased to 223 people in early 2018.